Gauge field theory approach to spin transport in a 2D electron gas - Berche, B.; Bolìvar, N.; López, A.; Medina, E. (Condensed Matter Physics, 2009)
We discuss the Pauli Hamiltonian including the spin-orbit interaction within an U(1) * SU(2) gauge theory
interpretation, where the gauge symmetry appears to be broken. This interpretation offers new insight into
the problem of spin currents in the condensed matter environment, and can be extended to Rashba and
Dresselhaus spin-orbit interactions. We present a few outcomes of the present formulation: i) it automatically
leads to zero spin conductivity, in contrast to predictions of Gauge symmetric treatments, ii) a topological
quantization condition leading to voltage quantization follows, and iii) spin interferometers can be conceived in
which, starting from an arbitrary incoming unpolarized spinor, it is always possible to construct a perfect spin
filtering condition. В рамках iнтерпретацiї U(1) * SU(2) калiбрувальної теорiї обговорюється гамiльтонiан Паулi, що включає спiн-орбiтальну взаємодiю, де калiбрувальна симетрiя порушується. Така iнтерпретацiя вiдкриває можливiсть проникнення в суть проблеми спiнових потокiв в конденсованому середовищi i може бути узагальнена на випадок спiн-орбiтальної взаємодiї Рашби та Дрессельхауса. Представлено кiлька висновкiв, що слiдують з такого формулювання: i) воно автоматично приводить до нульової спiнової провiдностi на вiдмiну вiд передбачень калiбрувально-симетричного пiдходу; ii) умова топологiчного квантування приводить до квантування напруги; iii) можна запропонувати спiновi iнтерферометри, в яких, починаючи з довiльного вхiдного неполяризованого спiнора, завжди можна утворити iдеальнi умови спiнового фiльтрування.